Caring for Coronavirus Healthcare Workers: Lessons Learned From Long-Term Monitoring of Military Peacekeepers - Gjerstad, Christer Lunde; Bøe, Hans Jakob; Falkum, Erik; Nordstrand, Andreas Espetvedt; Tønnesen, Arnfinn; Reichelt, Jon Gerhard; Lystad, June Ullevoldsæter (Frontiers in Psychology, 2020)
Background: The current outbreak of the coronavirus disease (COVID-19) is of unprecedented proportions in several regards. Recent reports suggest that many frontline healthcare workers (HCWs) suffer from mental health problems, including posttraumatic stress symptoms (PTSS). Previous studies have identified several key factors associated with short-term PTSS in pandemic HCWs, yet limited data is available on factors associated with long-term PTSS. Understanding the psychological impact of the pandemic on healthcare workers, is important in planning for future outbreaks of emerging infectious diseases. In the current study, we look to findings from a highly relevant subsection of the trauma field, the military domain. Objective: Pandemic HCWs and military peacekeepers may experience similar stressors in the line of duty. This study investigated whether factors linked to short-term PTSS in pandemic HCWs were also associated with long-term PTSS in military peacekeepers. Materials and Methods: Peacekeepers who reported pandemic-relevant stressors during deployment to a UN peacekeeping mission were included in the study (N = 1,627). PTSS was self-reported using the Posttraumatic Stress Disorder Checklist - Military Version. Descriptive instruments were used to assess possible factors associated with PTSS. A multiple linear regression analysis was performed to explore associations between these factors and PTSS. Results: Our model accounted for 50% of the variance in PTSS, F(1503,11) = 139.00, p < .001. Age, relationship- and employment status, as well as preparedness, working environment, social support after deployment, barriers to disclose, recognition, and loneliness, were all significantly associated with PTSS on average 30 years after deployment. The most important risk factors of long-term PTSS were personal barriers to disclose one’s experiences and current unemployment. Conclusions: Several factors linked to short-term PTSS in pandemic HCWs were associated with long-term PTSS in peacekeepers. We discuss how these findings may be used to prevent long-term PTSS in HCWs involved in the current COVID-19 outbreak.